European postgraduate curriculum in geriatric medicine developed using an international modified Delphi technique. (13th November 2018) - Roller-Wirnsberger, Regina; Masud, Tahir; Vassallo, Michael; Zöbl, Martina; Reiter, Raphael; Van Den Noortgate, Nele; Petermans, Jean; Petrov, Ignat; Topinkova, Eva; Andersen-Ranberg, Karen; Saks, Kai; Nuotio, Maria; et al.
Abstract: Background: the European Union of Medical Specialists (UEMS-GMS) recommendations for training in Geriatric Medicine were published in 1993. The practice of Geriatric Medicine has developed considerably since then and it has therefore become necessary to update these recommendations. Methods: under the auspices of the UEMS-GMS, the European Geriatric Medicine Society (EuGMS) and the European Academy of Medicine of Ageing (EAMA), a group of experts, representing all member states of the respective bodies developed a new framework for education and training of specialists in Geriatric Medicine using a modified Delphi technique. Thirty-two expert panel members from 30 different countries participated in the process comprising three Delphi rounds for consensus. The process was led by five facilitators. Results: the final recommendations include four different domains: 'General Considerations' on the structure and aim of the syllabus as well as quality indicators for training (6 sub-items), 'Knowledge in patient care' (36 sub-items), 'Additional Skills and Attitude required for a Geriatrician' (9 sub-items) and a domain on 'Assessment of postgraduate education: which items are important for the transnational comparison process' (1 item). Conclusion: the current publication describes the development of the new recommendations endorsed by UEMS-GMS, EuGMS and EAMA as minimum training requirements to become a geriatrician at specialist level in EU member states.